LEXICAL PROFILES IN EAP SPEAKING TASK PERFORMANCE - Noriko Iwashita (Universitas Katolik Indonesia Atma Jaya, 2008)
The present study investigates lexical competence in performance on speaking tests. It examines the extent to which learners preparing for tertiary study in English-speaking countries are able to demonstrate their ability to use a wide range of vocabulary in carrying out academic speaking tasks. Ninety-six task performances over four different tasks and two task types were drawn from three different levels. The performances were transcribed and analyzed using the WordSmith program (Scott, 2004). The results showed that test-takers’ vocabulary varied according to task and task type. The results of the study have implications for task design in academic speaking tests and teaching/learning vocabulary in EAP courses. Keywords: Lexical competence; Academic speaking test; Task types; EAP courses